PENGARUH LINGKUNGAN TERHADAP KREATIVITAS PEMBELAJARAN ANAK DI SMP NEGERI 20 MUARO JAMBI - resi adelina manulang (Universitas Batanghari Jambi, 2017)
Child creativity development is essential, children's creativity is developed by training children in certain skills according to their personal interests and given opportunities to develop their talents or talents. Hope to be achieved is to know the extent to which the influence of learning creativity, both internally and externally in Junior High School 20 Muaro Jambi. Testing data normality in a scientific research can be done by using Kolmogorov Smirnov Test (K-S Test) as a measure of the research instrument used as a benchmark in a study. Research and discussion can be stated that the influence of external environmental factors on children in school to support the creativity of learning in class VIII, IX at SMP 20 Muaro Jambi, with the value of external environmental factors (X2) based on SPSS version 20.00 obtained 0.019 (sig. 0.019